Immunogenicity and protective efficacy of tuzin protein as a vaccine candidate in Leishmania donovani-infected BALB/c mice - Devender, Moodu; Sebastian, Prince; Maurya, Vijay Kumar; Kumar, Krishan; Anand, Anjali; Namdeo, Madhulika; Maurya, Radheshyam (Frontiers in Immunology, 2024)
Visceral leishmaniasis (VL) is referred to as the most severe and fatal type of leishmaniasis basically caused by Leishmania donovani and L. infantum. The most effective method for preventing the spread of the disease is vaccination. Till today, there is no promising licensed vaccination for human VL. Hence, investigation for vaccines is necessary to enrich the therapeutic repertoire against leishmaniasis. Tuzin is a rare trans-membrane protein that has been reported in Trypanosoma cruzi with unknown function. However, tuzin is not characterized in Leishmania parasites. In this study, we for the first time demonstrated that tuzin protein was expressed in both stages (promastigote and amastigote) of L. donovani parasites. In-silico studies revealed that tuzin has potent antigenic properties. Therefore, we analyzed the immunogenicity of tuzin protein and immune response in BALB/c mice challenged with the L. donovani parasite. We observed that tuzin-vaccinated mice have significantly reduced parasite burden in the spleen and liver compared with the control. The number of granulomas in the liver was also significantly decreased compared with the control groups. We further measured the IgG2a antibody level, a marker of Th1 immune response in VL, which was significantly higher in the serum of immunized mice when compared with the control. Splenocytes stimulated with soluble Leishmania antigen (SLA) displayed a significant increase in NO and ROS levels compared with the control groups. Tuzin-immunized and parasite-challenged mice exhibit a notable rise in the IFN-γ/IL-10 ratio by significantly suppressing IL-10 expression level, an immunosuppressive cytokine that inhibits leishmanicidal immune function and encourages disease progression. In conclusion, tuzin immunizations substantially increase the protective immune response in L. donovani-challenged mice groups compared with control.